The Resilience of the Communist Party of China - Cunha, Luís (2022)
Upon reaching 100 years of activity, the Communist Party of China (CPC) highlights and projects a unique model of political and social development. Taking as methodological inspiration the proposal of Samuel P. Huntington for the study of the political phenomenon, regarding the adaptability of the seat of power, this work focus on some of the variables that justify the perpetuity of the CPC. Culture and ideology drive an unparalleled evolutionary process in conventional systemic frameworks, legitimized by an outfit with intrinsic Chinese characteristics. China's apparent exceptionalism, based on a strong nationalist vision, is conveyed through a transformational "new era." Western academic currents denote difficulty in framing this phenomenon with global implications.